Integrating Gemini AI into Islamic Moral Education: Implications for Students' Learning Outcomes - Navisa Ainina Mumtaz; Riza Faishol; Afrida Nur Laili; Vina Rohmatul Ummah (Al-Qalam Institue, 2026)
This study aimed to examine the effectiveness of Gemini AI-assisted learning in improving students’ understanding of Akidah Akhlak, particularly regarding social media ethics. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design. The participants consisted of 28 eighth-grade students selected through total sampling. Data were collected using an essay test instrument that met validity and reliability requirements, with a Cronbach’s Alpha coefficient of 0.745. Data analysis included the Shapiro–Wilk normality test, homogeneity test, paired-sample t-test, and effect size calculation. The findings indicated that the data met the assumptions of normality and homogeneity. The paired-sample t-test revealed a significant difference between pretest and posttest scores (p < 0.05), demonstrating a substantial improvement in students’ understanding after the implementation of Gemini AI-assisted learning. Furthermore, the effect size analysis produced a Cohen’s d value of 7.336, indicating a very large effect. These findings suggest that Gemini AI-assisted learning is highly effective in enhancing students’ understanding of social media ethics in Akidah Akhlak and highlight the potential of AI-based technologies as innovative pedagogical tools that can support more interactive, adaptive, and meaningful learning experiences in the digital era.